Performance Evaluation of WLAN network based TORA protocol using OFDM (802.11a) and Extended rate PHY (802.11g) (International Journal of Scientific Research and Management (IJSRM), 2016)
A mobile ad hoc network is a wireless network which do not have centralized control or preplanned infrastructure. MANET is a self organized and self configurable network where the mobile nodes move arbitrarily. In WLAN network all mobile nodes can sent and receive packets through routing. Routing is a critical issue in MANET and focus of this paper along with the performance analyses and evaluation of TORA routing protocol .Our simulation tool will be OPNET modeler. The performance of TORA routing protocol is analyzed by different matrices i.e. delay, network load, throughput, retransmission attempts, traffic sent and traffic received using WLAN based IEEE802.11a and IEEE802.11g with data rate of 24mbps and 36mbps